Determinants of firm value in the emerging economy: The roles of intellectual capital, financial performance and firm-specific characteristics - Truong, Hang Thanh; Le, Phong Ba; Dang, Ha Thu; Nguyen, Que Thi (Edelweiss Applied Science and Technology, 2026)
The purpose of this paper is to investigate the relationship between intellectual capital (IC) and firm value in an emerging economy, with a focus on the mediating role of financial performance and the moderating effect of firm-specific characteristics. This study uses panel data from 200 listed companies in Vietnam from 2017 to 2023 and employs structural equation modeling (SEM) combined with Dominance Analysis to assess the relative importance of factors and integrate causality research. The research findings indicate that financial performance plays a significant mediating role in transmitting the positive effect of IC on firm value, while the direct effect of IC is negative. This suggests that the value created by IC is not being fully recognized and reflected in stock prices in the short term. Among the components of IC, capital employed efficiency has the strongest contribution to firm value, followed by human capital efficiency and structural capital efficiency. The study, therefore, concludes that the key channel for transforming intellectual capital into firm value is improving the financial performance of businesses. The research results offer important practical implications for businesses in emerging markets in strategically investing in intellectual capital development, optimizing financial performance, and strengthening organizational structure to achieve sustainable firm value growth.